Handbook of research on Web 2.0, 3.0, and X.0 : technologies, business, and social applications - Murugesan, San. (Hershey, PA : Information Science Reference, 2010)
'This book provides a comprehensive reference source on next generation Web technologies and their applications'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Web 2.0.; Social media